Effects of Sheep Manure Combined with Chemical Fertilizers on Maize Yield and Quality and Spatial and Temporal Distribution of Soil Inorganic Nitrogen - Chun Yang; Wenbin Du; Lili Zhang; Zhaorong Dong (Complexity)
In order to explore the influences of sheep manure mixed with chemical fertilizers upon the yield and quality of maize and the spatial and temporal distribution of soil inorganic nitrogen under the wheat-maize rotation system, achieve increased yield and efficiency with rational fertilization of maize in this area, and at the same time provide a reasonable scientific basis for green production, an experiment was performed at Wanbei Comprehensive Experimental Station of Anhui Agricultural University in 2020 accordingly. The soil for the experiment is sand ginger black soil, and the subject is Zhengdan 958. The experiment adopts a randomized block design with 6 treatments: no fertilizer (T1), single application of the chemical fertilizer (T2), 15% sheep manure mixed with the chemical fertilizer (T3), 30% sheep manure combined with the chemical fertilizer (T4), 45% sheep manure added with the chemical fertilizer (T5), and only sheep manure (T6). The amount of nitrogen, phosphorus, and potassium applied in each treatment remains the same. The result of the experiment shows that T1 treatment has the lowest yield, followed by T6 treatment. The yield of sheep manure combined with the chemical fertilizer is much higher than that of pure sheep manure and no fertilizer. Among them, the yield of T3 is the highest and T4 is the lowest. There is no obvious variation between the combined treatments. Compared with single usage of the chemical fertilizer, the fat content of maize kernels treated with T3 and T4 is 8.9% and 5.6% higher than that of T2 treatment. The protein content of maize kernels treated with T3, T4, and T5 is 2.3%, 2.5%, and 2% higher than that of T2. It shows that the mixture of sheep manure and chemical fertilizer can improve the quality of maize kernels in some degree. The partial productivity of the nitrogen fertilizer in T3 and T5 treatments is 3.7% and 0.8% higher than that of T2 treatment, and the agronomic utilization rate of the nitrogen fertilizer is 10.9% and 1.6% higher than that of T2 treatment. T6 is much lower than that of T2 treatment. It certifies that the combined application of chemical fertilizers with sheep manure can increase the partial productivity and the agronomic utilization rate of the nitrogen fertilizer and increase crop yields and farmers’ income. The nitrate nitrogen of 40–60 cm soil layer is increased by 30.4%, 60–80 cm soil layer is increased by 56.5%, and 80–100 cm soil layer is increased by 11.6%. It shows that the mixed usage of organic and inorganic fertilizers can prevent nitrate nitrogen from moving to deep soil and reduce groundwater pollution.